Ectoparasites in Canis familiaris from Lages city, SC, Brazil and social-economical and cultural aspects of owners of family pets - Stalliviere, Fernanda Magalhães; Bellato, Valdomiro; Souza, Antonio Pereira de; Sartor, Amélia Aparecida; Moura, Anderson Barbosa de; Neidermaier, Luciana (Revista de Ciências Agroveterinárias, 2009)
The purpose of this research was to determine and compare the prevalence of ectoparasites in domiciliated dogs in the city of Lages, Santa Catarina State, southern Brazil, and to characterize the pet's family owners through social-economical and cultural aspects. Questionnaires were applied to the dog's owners from December of 2005 to December 2006. Ectoparasites from 143 dogs were collected and identified. The social-economical and cultural aspects were evaluated using data obtained from the income and schooling parameters. The ectoparasites prevalence in dogs was 22.9%. The ectoparasites prevalence in domiciliated dogs from the peripheral region was higher than in the central region. The owner cultural level did not affect dog's ecotoparasites prevalence.